Influence of Alkoxy Chain Length on the Properties of Two‐Dimensionally Expanded Azulene‐Core‐Based Hole‐Transporting Materials for Efficient Perovskite Solar Cells. Issue 27 (29th March 2019) - Truong, Minh Anh; Lee, Jaehyun; Nakamura, Tomoya; Seo, Ji‐Youn; Jung, Mina; Ozaki, Masashi; Shimazaki, Ai; Shioya, Nobutaka; Hasegawa, Takeshi; Murata, Yasujiro; Zakeeruddin, Shaik Mohammed; Grätzel, Michael; et al.
Abstract: A series of two‐dimensionally expanded azulene‐core‐based π systems have been synthesized with different alkyl chain lengths in the alkoxy moieties connected to the partially oxygen‐bridged triarylamine skeletons. The thermal, photophysical, and electronic properties of each compound were evaluated to determine the influence of the alkyl chain length on their effectiveness as hole‐transporting materials (HTMs) in perovskite solar cells (PSCs). All the synthesized molecules showed promising material properties, including high solubility, the formation of flat and amorphous films, and optimal alignment of energy levels with perovskites. In particular, the derivatives with methyl and n ‐butyl in the side chains retained amorphous stability up to 233 and 159 °C, respectively. Such short alkoxy chains also resulted in improved electrical device properties. The PSC device fabricated with the HTM with n ‐butyl side chains showed the best performance with a power conversion efficiency of 18.9 %, which compares favorably with that of spiro‐OMeTAD‐based PSCs (spiro‐OMeTAD=2, 2′, 7, 7′‐tetrakis[ N, N ‐bis( p ‐methoxyphenyl)amino]‐9, 9′‐spirobifluorene). Abstract : Improved efficiencies . Two‐dimensionally expanded azulene‐core‐based π systems with different alkyl chain lengths in the alkoxy moieties connected to the partially oxygen‐bridged triarylamine skeletons have been synthesized (see figure). The influence of the alkyl chain length on their thermal, photophysical, and electronic properties has also been investigated. Perovskite solar cells fabricated by using these materials as hole‐transporting materials showed power conversion efficiencies of up to 18.9 %.